2008
DOI: 10.1080/17451000801964923
|View full text |Cite
|
Sign up to set email alerts
|

Biology and interspecific interactions of the alien crabPercnon gibbesiin the Maltese Islands

Abstract: Spatial and bathymetric distribution, population density, habitat preferences, fecundity, breeding season and interspecific interactions of the alien grapsoid crab Percnon gibbesi (H. Milne-Edwards, 1853) from the Maltese Islands (Malta and Gozo) are compared among localities in the Mediterranean where established populations have been reported since 1999. In the Maltese Islands, habitat preferences and bathymetric distribution were similar to those in other Mediterranean localities. Spatial distribution was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…In fact, P. marmoratus mainly inhabits supralittoral crevices (Augusto andFlores 2001, Deudero et al 2005), whereas P. gibbesi shows no tendency towards a semi-terrestrial lifestyle, with limited bathymetric distribution restricted to the infralittoral zone from 0 to 4 m depth. Laboratory experiments indicated that when competing for space, P. marmoratus dominates the interactions with P. gibbesi (Sciberras and Schembri 2008). The present results provide new biochemical evidence suggesting that P. gibbesi and P. marmoratus do not compete for space and there is no spatial overlap, so P. marmoratus is not excluded from its natural habitat by the alien species.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In fact, P. marmoratus mainly inhabits supralittoral crevices (Augusto andFlores 2001, Deudero et al 2005), whereas P. gibbesi shows no tendency towards a semi-terrestrial lifestyle, with limited bathymetric distribution restricted to the infralittoral zone from 0 to 4 m depth. Laboratory experiments indicated that when competing for space, P. marmoratus dominates the interactions with P. gibbesi (Sciberras and Schembri 2008). The present results provide new biochemical evidence suggesting that P. gibbesi and P. marmoratus do not compete for space and there is no spatial overlap, so P. marmoratus is not excluded from its natural habitat by the alien species.…”
Section: Discussionsupporting
confidence: 48%
“…These characteristics suggest that the ecological niche of P. gibbesi does not interfere with that of other benthic organisms such as P. marmoratus (Deudero et al 2005). Moreover, previous studies have found no competitive interactions between P. gibbesi and P. marmoratus that could be a consequence of their physiological status and this finding is also supported through biochemical analysis (Deudero et al 2005, Sciberras andSchembri 2008). We hypothesize that aerial exposure could result in increased antioxidant enzymes and vitamin E content as a response to UV radiation and atmospheric oxygen.…”
Section: Introductionmentioning
confidence: 56%
“…It is a primarily algivorous crab of the shallow infralittoral rocky shores (usually < 4 m depth) and may reach densities of 10 ind. m 2 (Sciberras & Schembri 2008, Raineri & Savini 2010. Its widespread and expanding distribution along the Mediterranean coasts and the high rates of increase in abundance denote a highly invasive species ).…”
Section: Discussionmentioning
confidence: 97%
“…While some aspects of the biology and ecology of adult P. gibbesi have been investigated [25][26][27][28][29][30], little is known on its larval stages. A major reason could be the low efficiency of traditional sampling gear (e.g., plankton nets) in collecting a sufficient number of living and healthy larvae.…”
Section: Open Accessmentioning
confidence: 99%